Proposição de um método para desenvolvimento de sistema de apoio à decisão baseado em modelos de simulação computaciona na indústria de mineração - Camargo, Luis Felipe Riehs (Universidade do Vale do Rio dos Sinos, 2013)
Decisions are essential for the maintenance and growth of the firm in competitive and uncertain environment. Decisions are also important and difficult to be taken due to the uncertainty of their future potential results. This dissertation tries to fill a gap in the literature of modeling and simulation methods to support operations decisions and setting operating policies in the operations. There are few approaches at the specialized OR/MS literature that integrate the production system and the manufacturing system and provide system performance in terms of quality the product and productivity of the system. This dissertation presents a method for the construction of a decision support system, based on systems thinking (soft OR) and computer simulation (hard OR). The method allows evaluating dynamically, stochastic and systemic the impact of the decisions of the supply chain in the mining area and deal with the phenomenon of degradation and variability in the quality of the raw material. The application of the method on a real case demonstrated to be feasible. The dissertation also illustrated situations in which the simulation model was used to support decisions at Samarco Company. The study further demonstrates, with the computational model developed, the effect of the degradation of the quality of raw material in the overall system performance.
Keywords: Simulação computacional; Pensamento sistêmico; Modelagem matemática; Indústria de mineração; Computational simulation; Mining industry; Systems thinking; Mathematical modeling; ACCNPQ::Ciências Sociais Aplicadas::Administração